UTILIZATION OF ACCOUNTING PRACTICES BY OWNERSOFSMALL AND MEDIUM SCALE ENTERPRISES FORBUSINESSSUCCESS IN ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
This study ascertained the extent of utilization of accounting practices by owners of small andmedium-scale enterprises for business success in Anambra State, and this was necessitated bytheneed to ensure that SMEs keep proper books of accounts and put adequate maintenance and controlmeasures. Two research questions guided the study and two null hypotheses were tested. Descriptivesurvey research design was adopted for the study. The population comprised all 2,050 registeredowners of SMEs in Anambra State. Sample size of 615 was used, through proportionate stratifiedrandom sampling technique. A 22-item structured questionnaire was used. The instrument wasvalidated by three experts. Cronbach Alpha was used to determine the internal consistency of theinstrument and obtained an overall coefficient value of 0.86. Mean and standard deviation were usedto answer the research questions, while Analysis of Variance (ANOVA) was used to test the nullhypotheses at 0.05 level of significance. The findings of the study revealed that bookkeeping practiceswas greatly utilized, while the auditing practices are moderately utilized. The owners of SMEs differsignificantly in their mean ratings on the extent they utilized bookkeeping accounting and auditingpractices based on type of enterprises. The study concluded that auditing practices was not widelyused which is as a result of SMEs owners’ inability to determine its important in promotingeffectiveness in recording of business transactions systematically and more accurate for financialreports. It was therefore recommended among others that, owners of SMEs in Anambra State shouldutilized auditing practices to a great extent because it will enable them have great influence onconsumer’s perception of product and services as an incentive to consumers to patronized theirproduct.
Keywords: Utilization, Accounting Practices, Owners, Small and Medium-Scale Enterprises